Are bond markets really overpriced: The case of the US - Jörg Clostermann; Franz Seitz (Fachhochschule Ingolstadt - University of Applied Sciences, 2005)
In the present paper we analyse whether fundamental macroeconomic factors, temporary influences or more structural factors have contributed to the recent decline in bond yields in the US. For that purpose, we start with a very general model of interest rate determination in which risk premia are captured via the macroeconomic (policy) environment. The empirical part consists of a cointegration analysis with an error correction mechanism from the mid 80s until 2005. We are able to establish a stable long-run relationship and find that the behaviour of bond rates in the last few years may well be explained by macroeconomic factors. These are driven by core price developments, monetary policy reflected in short-term interest rates and the business cycle. A changed structural demand for bonds does not seem to be at work. The existing overestimation of bond yields is not unusual historically. Finally, our bond yield equation outperforms a random walk model in different out-of-sample exercises.
urn:nbn:de:bvb:573-265
Keywords: C32; E43; E47; 650; bond yields; interest rates; cointegration; inflation; forecasting